Predictors of psychosocial adjustment in siblings of children with autism spectrum disorder: a structural equation modeling study - İlçioğlu Ekici, Gökçen and Kılıç, Birim Günay (The Turkish Journal of Pediatrics, 2026)
Background. Siblings of children with autism spectrum disorder (ASD) are at increased risk of psychosocial difficulties due to altered family dynamics and parental stress. However, the mechanisms linking ASD severity, parental psychopathology, and sibling outcomes remain unclear. This study aimed to identify determinants of psychosocial problems among siblings of children with ASD using a family-systems framework and structural equation modeling (SEM). Methods. A case–control study was conducted with 67 siblings of children with ASD (ASD-Sibs) and 67 siblings of typically developing children (TD-Sibs), aged 6–18 years. ASD severity was rated using the Childhood Autism Rating Scale (CARS). Sibling depression, anxiety, and emotion regulation were assessed using the Child Depression Inventory (CDI), Screen for Child Anxiety Related Emotional Disorders (SCARED), and Cognitive Emotion Regulation Questionnaire (CERQ). Parents completed the Child Behavior Checklist (CBCL), Beck Depression and Anxiety Inventories (BDI, BAI), and Family Assessment Device (FAD). SEM was used to examine predictors of sibling psychosocial outcomes. Results. ASD-Sibs reported significantly higher depressive and anxiety symptoms than TD-Sibs. SEM revealed that maternal depression and general family functioning were significant predictors of sibling depression, anxiety, and behavioral problems. ASD severity indirectly influenced sibling outcomes through maternal depression and anxiety. Positive reappraisal emerged as a protective factor against anxiety. Conclusions. Maternal psychological well-being and family functioning are key determinants of psychosocial adjustment among ASD-Sibs. Autism severity affects siblings indirectly via maternal psychopathology, underscoring the importance of holistic, family-centered interventions to promote resilience in families of children with ASD.